A novel dealloying strategy for fabricating nanoporous Ag via ζ′-AgGa alloy. (7th May 2022) - Jiang, Zhongming; Zhang, Jiamin; Wang, Kaizhao; Chen, Tianyou; Zhao, Jiuwei; Wang, Kaijun; Hu, Jin
Abstract: A mild strategy for fabricating nanoporous silver (np-Ag) pieces was reported via preparation of Ag–Ga alloys in relatively low temperature and subsequent electrochemical dealloying in nitric acid (HNO3 ) aqueous solution. After selectively etching Ga out of the Ag–Ga alloy, a typical three-dimensional (3D) bicontinuous nanoporous structure with a pore size of ∼67.21–159.33 nm was observed. A series of studies have shown that the addition of sodium dodecyl sulfate (SDS) results in minimum pore size. The coarsen exponent ( n ) is 1.61, and the activation energy was calculated to be 27.04 kJ mol −1 . The ζ ′-AgGa alloy prepared at low temperature can be used as the precursor for the preparation of fine np-Ags, and this method provides a new strategy for the industrial production of dealloyed np-Ag.